Korean Society of Heart Failure Guidelines for the Management of Heart Failure: Treatment - Youn, Jong-Chan; Kim, Darae; Cho, Jae Yeong; Cho, Dong-Hyuk; Park, Sang Min; Jung, Mi-Hyang; Hyun, Junho; Cho, Hyun-Jai; Park, Seong-Mi; Choi, Jin-Oh; Chung, Wook-Jin; Yoo, Byung-Su; et al. (International journal of heart failure, 2023)
The Korean Society of Heart Failure (KSHF) guidelines aim to provide physicians with evidence-based recommendations for the management of patients with heart failure (HF). After the first introduction of the KSHF guidelines in 2016, newer therapies for HF with reduced ejection fraction, HF with mildly reduced ejection fraction, and HF with preserved ejection fraction have since emerged. The current version has been updated based on international guidelines and research data on Korean patients with HF. Herein, we present Part II of these guidelines, which comprises treatment strategies to improve the outcomes of patients with HF.